Which expression is equivalent to (fg) (5)? F(5)* g(5) F(5)+g(5) 5f(5) 5g(5)

Question

Which expression is equivalent to
(fg) (5)?
F(5)* g(5)
F(5)+g(5)
5f(5)
5g(5)

in progress 0
Delwyn 5 months 2021-08-24T04:14:53+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-24T04:16:17+00:00

    Answer:

    they F (5) g (5)

    Step-by-step explanation:

    (fg)=(f.g)

    and then this is the first doing (fg)(X)= f(x) [g(x)]

    x=5

    f(5).g(X)

    and they final result is

    they top of answer

    happy answering

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )